2007
DOI: 10.1667/rr0527.1
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Carcinogenesis in Patients Treated with Radiation: A Review of Data on Radiation-Induced Cancers in Human, Non-human Primate, Canine and Rodent Subjects

Abstract: Concern for risk of radiation-induced cancer is growing with the increasing number of cancer patients surviving long term. This study examined data on radiation transformation of mammalian cells in vitro and on the risk of an increased cancer incidence after irradiation of mice, dogs, monkeys, atomic bomb survivors, occupationally exposed persons, and patients treated with radiation. Transformation of cells lines in vitro increased linearly with dose from approximately 1 to approximately 4-5 Gy. At <0.1 Gy, tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
148
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(158 citation statements)
references
References 93 publications
4
148
0
4
Order By: Relevance
“…The question of secondary tumors, as a succession of radiotherapy, was investigated in several recent studies [Suit et al, 2007, Trott K-R., 2009, Tubiana M., 2009, Xu et al, 2008. Based on epidemiological and experimental radiobiological data, Suit et al (2007) concluded that the relationship of tumor induction risk and dose is complex and differs not only between species of animals, between individuals of the species concerned, but it may also be different for various tissues and organs. Specifically, the risk increases with dose in the 1-45 Gy range for gastric and pancreatic cancer, but is stable in the 1-60 Gy dose range for bladder cancer, and even negative for colon cancer.…”
Section: The Potential Clinical Consequences Of Radiation Induced Bysmentioning
confidence: 99%
“…The question of secondary tumors, as a succession of radiotherapy, was investigated in several recent studies [Suit et al, 2007, Trott K-R., 2009, Tubiana M., 2009, Xu et al, 2008. Based on epidemiological and experimental radiobiological data, Suit et al (2007) concluded that the relationship of tumor induction risk and dose is complex and differs not only between species of animals, between individuals of the species concerned, but it may also be different for various tissues and organs. Specifically, the risk increases with dose in the 1-45 Gy range for gastric and pancreatic cancer, but is stable in the 1-60 Gy dose range for bladder cancer, and even negative for colon cancer.…”
Section: The Potential Clinical Consequences Of Radiation Induced Bysmentioning
confidence: 99%
“…5,22 Suit et al reviewed the data on radiation-induced cancers from mammalian cells in vitro and animal and human studies. 23 Transformation of cell lines in vitro increased linearly with dose from 1 to 5 Gy. Radiation-induced DNA mutation appears to be the initial carcinogenic event leading to aberrant expression of oncogenic and tumor suppressor genes.…”
Section: Discussionmentioning
confidence: 99%
“…8,[10][11][12][13][14][15][16][17][18][27][28][29] The consequences of radiation exposure vary in different animals and even different strains of the same species, and in organs within a species. 23 The development of secondary cancer may not be related to radiotherapy, but rather may be explained by diagnostic bias, common etiologic factors, or by common pathway of carcinogenesis. 30 Some tumor registry [27][28][29] and institutional 11,14 based studies have not demonstrated an increased bladder cancer risk in prostate cancer patients who received radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Although the two contouring methods (AIP and REF) for conventional 3D dose calculation result in significant differences in predicted healthy organ doses (several tens of percent), there was ultimately no strong trend for over‐ or underprediction of doses to particular organs. This negates the possibility of applying generic correction factors (or similar approaches) to doses estimated using AIP‐based 3D methods, and implies that, particularly for sensitive patient groups, 36 , 37 , 38 , 39 the 4D method ought to be employed. In the long term, it would be preferable for the 4D approach to be employed for all patients, such that accurate dose‐outcome correlation can be recorded and accurate tissue complication probabilities be established.…”
Section: Discussionmentioning
confidence: 99%